Analytic theology new essays in the philosophy of theology - Crisp, Oliver 1972-; Rea, Michael C. 1968- (Oxford Oxford University Press, 2009)
The methodological divide between systematic theologians and analytic philosophers of religion is ripe for exploration. The present volume represents an attempt to begin a much-needed interdisciplinary conversation about the value of analytic philosophical approaches to theological topics.
Keywords: Philosophical Theology; Philosophical Theology; Aufsatzsammlung